Therapeutic touch and postmodernism in nursing - Glazer, Sarah (Nursing philosophy, 2001)
Therapeutic touch, a healing technique based upon the laying-on of hands, has found wide acceptance in the nursing profession despite its lack of scientific plausibility. Its acceptance is indicative of a broad antiscientific trend in nursing. Adherents of this movement use the jargon of postmodern philosophy to justify their enthusiasm for a variety of mystically based techniques, citing such postmodern critics of science as Derrida and Michel Foucault as well as philosophical forerunners Heidegger and Husserl. Between 1997 and 1999, 94 articles in nursing journals referred to postmodernism, according to a database search. This paper criticizes the postmodern movement for abandoning the biological underpinnings of nursing and for misreading philosophy in the service of an antiscientific world-view. It is also suggested that nursing can retain its tradition of ‘caring’ without abandoning the scientific method.